Good Governance Dalam Mengukur Kinerja Lembaga Negara (Review) - Jefirstson Richset Riwukore; Fellyanus Habaora; Terttiaavini Terttiaavini (UNIVERSITAS INDO GLOBAL MANDIRI, 2022)
This study aims to encourage the realization of good governance as accountability and transparency of the performance of state institutions. This study uses a literature review method which is analyzed descriptively. The data source used is secondary data. This scientific study was conducted for 2 (two) months, namely July-August 2020. The process of preparing the report was carried out by referring to the research stages of data collection, data reduction, data presentation, and drawing conclusions. Based on the results of this study, efforts to realize good governance epistemologically can only be implemented in five universal principles, namely: responsibility, accountability, fairness, independence, and transparency. Strategies to encourage accountability and transparency of the performance of state institutions to achieve good governance can be carried out through strengthening the basis for supporting state institutions' performance instruments, strengthening performance-based budgeting and monitoring the performance of state institutions. Recommendations that can be made are: (1) setting up the instrument model for the performance of state institutions in accordance with the principles of good governance; (2) setting and developing a performance-based budget system to monitor and evaluate performance in accordance with the principles of good governance; and (3) innovative role models for monitoring the performance of state institutions. Keywords : good governance, accountability, transparency, state institutions